PENGEMBANGAN BAHAN AJAR MULTIMEDIA BERBASIS MULTIPLE INTELLIGENCES DAN NILAI-NILAI PANCASILA - Febrianti Yuli Satriyani (Nurul Jadid University, 2018)
The purpose of this study is to produce multimedia based on multiple intelligences and Pancasila values in the Educational Psychology course which: (1) is theoretically valid, (2) has a level of implementation, (3) attractiveness, and (4) high usefulness , and (5) effective in achieving learning objectives. This research includes development research. This study uses a simplification development model from Borg & Gall which includes: (1) preliminary study, (2) planning, (3) product design, (4) product validation, (5) product testing, and (6) final product. At the planning stage and product testing, the researcher is more clear to use a few modified steps from Dick & Carey. The results showed that the multimedia developed had very valid values with a percentage of achievement of 92%, had a very good level of implementation with 93% achievement percentage, 95% attractiveness rate, very useful with 92% achievement percentage and very effective with 95% achievement percentage to achieve the learning objectives in the material of human development theory, which is Educational Psychology.